İneklerde klinik muayene ve progesteron test kitleri ile yapılan östrus teşhisinin gebelik oranları üzerine etkisi (The Effect of Esrrus Detection by Progesterone Test Kits and Clinical Examination on Conception Rates in Cows) - Sönmez, M; Türk, G; Demirci, E (My University, 2006)
This study was conducted to compare the effect of estrus detection using progesterone test kits and clinical examination on the conception rate, and to investigate whether the progesterone tests have positive effect on conception rate of cows in field conditions. A total of 136 cows were used in this study. The clinical findings of estrus in cows were examined by visual observation and rectal palpation. Cows were divided into three subgroups considering to the intensity of clinical results. Progesterone levels in serum samples were evaluated using progesterone test (Ovulation Test®) kits. Cows were also divided into three subgroups according to the progesterone levels, and then, all cows were artificially inseminated. The conception rates were determined by rectal palpation on 55-60th days following artificial insemination. In this study, the mean overall conception rate was recorded as 65.4%. It has been found that there is no difference (p>0.05) among conception rates of cows which were divided into subgroups by intensity of clinical findings. The conception rates were significantly (p<0.05) higher in cows with low concentrations of progesterone (<1 ng/ml) at insemination time than those of cows with intermediate concentrations of progesterone (1-2.5 ng/ml) (78.5% vs. 23.8%). In addition, the conception didn’t occur in cows with high concentrations of progesterone (>2.5 ng/ml). In conclusion, the use of practice progesterone tests can be useful for preventing errors in heat detection and for increasing conception rate in cows which not be detected in estrus by clinical examination.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: İnek Östrus teşhisi Gebelik oranı Klinik muayene Progesteron (Cow Estrus detection Conception rate Clinical examination Progesterone)